Investigation of pressure drop over textured surfaces - Huang, Huolin (2018)
The rising fuel cost has inspired many researchers to develop effective drag reduction methods, one of which was to investigate the optimal size and geometry of the riblet to achieve the objective. Despite a range of 5% to 10% in drag reduction was found by numerous researchers, the physical mechanism of riblets remains little known. In this work, randomized longitudinal riblets produced by sandpapers with different grit sizes were investigated in a close-loop wind tunnel, the experiment was designed to elevate the textured surfaces from the wind tunnel wall at zero pressure gradient. Despite the dimension of the textures were not proportional to the grit size of the sandpaper used, pressure drop reduction was detected for all the nine textured surfaces in turbulent flow, whereas the pressure drop reduction was fairly negligible in laminar region. The results are conclusive to suggest that the pressure drop reduction is closely related to the height-to-spacing (h/s) ratio of the riblets. Of all the nine textured surfaces examined, the results showed a maximum reduction of 42.4% in pressure drop for a h/s ratio at approximately 0.1, the trend of the results showed the pressure drop reduction increases with the h/s ratio. Additionally, recommendations for related future research work have been proposed, particularly for producing larger h/s ratios in hopes of attaining higher pressure drop reduction.